2010
DOI: 10.5650/jos.59.541
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonic-Hydroxyl-Type Heterogemini Surfactants Synthesized from Unsaturated Fatty Acids

Abstract: Novel anionic heterogemini surfactants have been synthesized from two kinds of unsaturated fatty acids (oleic acid and petroselinic acid). The hydrocarbon chain is covalently bound to the terminal carbonyl group of the unsaturated fatty acids and hydrophilic headgroups (i.e., sulfonic and hydroxyl groups) are introduced to the cis double bond. The aqueous solution properties of the surfactants synthesized here have been studied on the basis of static/dynamic surface tension, conductivity, fl uorescence, and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The surfactants exhibit pH-dependent protonation-deprotonation behavior in aqueous solutions. In alkaline solutions, the surfactants lower the surface tension as well as forming molecular assemblies, even in the region of relatively low concentrations, in a manner similar to oleic acid-based gemini surfactants with phosphate 5 or sulfonic 6 acid headgroups. Under acidic or neutral conditions, the surfactants are intrinsically insoluble in the aqueous media and form a monolayer at the air/water interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfactants exhibit pH-dependent protonation-deprotonation behavior in aqueous solutions. In alkaline solutions, the surfactants lower the surface tension as well as forming molecular assemblies, even in the region of relatively low concentrations, in a manner similar to oleic acid-based gemini surfactants with phosphate 5 or sulfonic 6 acid headgroups. Under acidic or neutral conditions, the surfactants are intrinsically insoluble in the aqueous media and form a monolayer at the air/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…The two carboxylic acid headgroups are introduced to the cis double bond of oleic acid. This is a remarkable feature of CC-9,9-Esn since oleic acid-based surfactants that we have synthesized in the past exhibit a dissymmetric headgroup structure 5,6 . The symmetric headgroups in our current samples exclude the presence of possible regioisomers, although pairs of enantiomers 9R,10R and 9S,10S must be present in view of the reaction mechanism.…”
Section: Molecular Characteristicsmentioning
confidence: 99%
“…The products we have developed in the past include anionic phosphate-type 5 , sulfonate-type 6 , carboxylatetype 7 , and cationic quaternary ammonium-type 8 surfactants. In these papers, we reported not only the syntheses of these surfactants but also their dilute aqueous solution properties as a function of the length of the hydrocarbon chain covalently bound to the terminal carbonyl group of the oleic acid 5 8 .…”
mentioning
confidence: 99%
“…In these papers, we reported not only the syntheses of these surfactants but also their dilute aqueous solution properties as a function of the length of the hydrocarbon chain covalently bound to the terminal carbonyl group of the oleic acid 5 8 . In addition, from the physicochemical standpoint, we studied the effects of molecular symmetry on the dilute aqueous solution properties using the sulfonate-type surfactants synthesized from oleic acid and petroselinic acid 6 , the characteristics of an insoluble monolayer film formed at the air/water interface using the carboxylate-type surfactants under acidic or neutral conditions 7 , and the adsorption characteristics of the cationic surfactants that occur at the silica/aqueous solution interface 8 .…”
mentioning
confidence: 99%
“…The presence of such vesicular assemblies has also been confi rmed on the basis of dynamic light scattering DLS data 10 . Our recent studies focusing on the sulfonic-type gemini surfactants synthesized from oleic acid and petroselinic acid have suggested that the adsorption and molecular association capabilities are infl uenced not only by the hydrocarbon chain length, but also by the molecular symmetry i.e., the ratio of the two hydrophobic chain lengths 8,11 .…”
Section: Oleic Acid-based Gemini Surfactantsmentioning
confidence: 99%